Pengaruh Implementasi CSR PT Pelabuhan Indonesia (Persero) Regional 2 Panjang Terhadap Kesejahteraan Masyarakat - Annisa Femiya; Toto Gunarto (Journal on Education, 2023)
The aim of this research is to determine the effect of implementing the CSR program of PT Pelabuhan Indonesia (Persero) Regional 2 Panjang on the welfare of the community in the environment around the company located in Panjang District. The population in this research is all communities that have a partnership contract with PT Pelabuhan Indonesia (Persero) Regional 2 Panjang and who directly experience the implementation of the environmental development program around their residence, totaling 100 heads of families. The locations in this research are people who live in Panjang District in the districts of Panjang Selatan, Panjang Utara, Karang Maritim, and Pidada. The analysis used in this research is parametric non-linear regression analysis, namely ordered probit. Based on the research results, it shows that the CSR program has a significant positive and negative effect on the welfare of the community around the company PT Pelabuhan Indonesia (Persero) Regional 2 Panjang.